Peningkatan Perilaku Sanitasi Masyarakat Desa Handio Melalui Edukasi dan Optimalisasi Fasilitas Kamar Mandi - Lailan Aprina Siregar; Nurhalima Lubis; Nur Hasanah Nasution; Rafida Wahyuni Lubis; Saipul Anwar Hasibuan; Wilham Saputra; Yanti Hotmaida Harahap; Zaharo Arjuna Hasibuan (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Sanitation is a crucial aspect of maintaining public health and creating a clean, healthy living environment. Community practices regarding bathroom cleanliness and the proper use of available sanitation facilities play a vital role in fostering a healthy environment. This initiative aims to enhance the understanding and practices of the Handio village community regarding sanitation hygiene through education and by optimizing the use of bathroom facilities. The methods employed included observing sanitation conditions, providing community education, demonstrating bathroom cleaning practices, and offering guidance on the use of sanitation facilities. The activity was conducted as part of a student field study program (KKL) in Handio Village, Ulu Sosa District, Padang Lawas Regency. The results indicate an increased community understanding of the importance of maintaining a clean local environment. Direct education and guidance serve as effective strategies to encourage behavioral changes regarding sustainable environmental sanitation.